Handbook of alternative materials in residential construction - Bynum, Rychard T., Jr. (McGraw-Hill, 1999)
This book is about: The accessible home; Foundations and basements; Floors and floor systems; Wall and roof structures; Siding, Cladding & Roofling; Windows and exterior doorss; Interior doors and hardware; Interior partitions; Heating and air conditioning; Plumbing and sprinkler systems; and Electrical systems and accessories.